Masked Bobwhite: Status of an Endangered Subspecies - Robert Mesta (National Quail Symposium Proceedings, 2017)
The masked bobwhite (Colinus virginianus ridgwayi), first collected in 1884, soon disappeared and was considered extinct by 1950. Its rediscovery in 1964 precipitated an aggressive effort to restore the masked bobwhite within its range in both the United States and Mexico. The masked bobwhite, despite this effort, has continued to decline with a precipitous decrease in numbers in the last decade. Surveys conducted in 2009 and 2010 resulted in no detections; for all practical purposes the masked bobwhite is now extinct in the wild. Fortunately, a captive population continues to exist and with proper management can produce sufficient masked bobwhite to restore the wild population. The Masked Bobwhite Recovery Program has been developed and is implementing a bi-national recovery strategy with Mexican cooperators that includes: (1) construction of a new captive breeding facility on Buenos Aires National Wildlife Refuge and adoption of new husbandry and rearing protocols; (2) contracting with the San Diego Zoo Conservation Research Center to manage and operate the new facility; (3) construction of a new facility at Africam Safari, Puebla, Mexico; (4) creation of a reintroduction program in Sonora, Mexico; (5) development of a Mexican landowner outreach program; and (6) a habitat improvement and predator management program on Buenos Aires National Wildlife Refuge.
Keywords: Arizona; Colinus virginianus ridgwayi; masked bobwhite; Mexico; recovery strategies